2020
DOI: 10.1007/s11661-020-05626-2
|View full text |Cite
|
Sign up to set email alerts
|

On the Precipitation-Strengthening Contribution of the Ta-Containing Co3(Al,W)-Phase to the Creep Properties of γ/γ′ Cobalt-Base Superalloys

Abstract: The creep strength of single-crystalline Co-based superalloys was found to be comparable to first-generation Ni-base superalloys. However, considerable shearing of the c¢ precipitates was observed in the early creep stages. To determine the strengthening contribution of the Ta-containing c¢-Co 3 (Al,W) precipitates, the creep strength of several single-crystalline CoAl -W-Ta superalloys was determined as a function of the c¢ volume fraction at 1223 K (950°C) and stress levels between 25 and 600 MPa. Employing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 40 publications
1
14
0
Order By: Relevance
“…The Co-base superalloy system that is investigated in this work is designed to vary the volume fraction of the γ′-phase without varying the composition of the individual phases, γ and γ′ [33]. This peculiarity is supposed to be obtained by conducting compositional changes along a schematic tie-line in a Co-(Al,W,Ta) quasi-binary system [33].…”
Section: Sample Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Co-base superalloy system that is investigated in this work is designed to vary the volume fraction of the γ′-phase without varying the composition of the individual phases, γ and γ′ [33]. This peculiarity is supposed to be obtained by conducting compositional changes along a schematic tie-line in a Co-(Al,W,Ta) quasi-binary system [33].…”
Section: Sample Materialsmentioning
confidence: 99%
“…The Co-base superalloy system that is investigated in this work is designed to vary the volume fraction of the γ′-phase without varying the composition of the individual phases, γ and γ′ [33]. This peculiarity is supposed to be obtained by conducting compositional changes along a schematic tie-line in a Co-(Al,W,Ta) quasi-binary system [33]. According to [33], the four alloys in this work are based on exhibited nominal volume fractions of 20% γ′ (referred to as VF20 in the following), 40% γ′ (VF40), 50% γ′ (VF50) up to 60% γ′ (VF60) after heattreatment.…”
Section: Sample Materialsmentioning
confidence: 99%
“…Their strength even exceeds that of some precipitation-strengthened Ni-base superalloys. [1][2][3] Thus, they are regarded as potential structural materials for future turbine engine applications. [4][5][6] Although this new alloy system was rediscovered just over 1 decade ago, [4] the knowledge regarding the effect of alloying elements, [7][8][9][10][11] oxidation, [12][13][14] and thermodynamic, [15][16][17][18] microstructural, [3,19,20] and mechanical properties [2,[21][22][23] has significantly increased since then.…”
Section: Introductionmentioning
confidence: 99%
“…This enables the investigation of the microstructure as well as the thermodynamic and thermophysical properties of the Co-Al-W-Ta alloys as a function of the c¢ volume fraction with the same chemical and physical properties of the constituent phases. In a previous publication, [41] we already presented the creep properties of these alloy series. We found that the strengthening contribution of the c¢ phase correlates with its volume fraction, that is, an increasing c¢ volume fraction provides a higher strengthening contribution and, subsequently, a higher creep resistance.…”
Section: Introductionmentioning
confidence: 99%
“…The Co-base model superalloy with γ/γ'-microstructure used in this work is based on the quaternary Co-Al-W-Ta system. According to its intended γ'-Volume Fraction of 40%, the name "VF40" was given by Bezold et al who initially designed the alloy as part of a larger series of which the volume fraction was systematically varied [34]. The oxidation behaviour of VF20, VF40, VF50, and VF60 was recently investigated in detail [18].…”
Section: Sample Materialsmentioning
confidence: 99%